1983
DOI: 10.1007/bf00291540
|View full text |Cite
|
Sign up to set email alerts
|

Types and subtypes of haptoglobin in the Chinese population

Abstract: Haptoglobin phenotypes of 1121 unrelated Chinese blood donors in Beijing were determined. The gene frequency of Hp1 was 0.270. A rare variant, which we identified as Hp1S-J, was found. Two hundred and two samples of this population were submitted to haptoglobin subtyping, and no Hp1F allele was found among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…21 In contrast, the frequency of the 1 to 1 phenotype has been found to be lower in Asian populations, while the frequency of 2 to 2 is higher. 1,10,22 The findings from the current study regarding phenotype distribution are in agreement with those previously reported.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…21 In contrast, the frequency of the 1 to 1 phenotype has been found to be lower in Asian populations, while the frequency of 2 to 2 is higher. 1,10,22 The findings from the current study regarding phenotype distribution are in agreement with those previously reported.…”
Section: Discussionsupporting
confidence: 96%
“…1 In normal aortas, the lamellar structure of media is the thickest layer and is an orderly array of collagen, elastin, and smooth muscle cells. Degeneration of this matrix leads to destruction of the media and adventia, which in turn results in gradual aortic dilation.…”
mentioning
confidence: 99%
“…The Chinese of Hong Kong have a higher frequency of Hp' (0.38) (Mourant et al, 1976). Hp' frequency of 0.27 has been reported in the Han Chinese from Beijing and Shanghai, respectively, by Liang et al (1983) and Kong et al (1983). Variable frequencies ofHp' have also been reported in ethnic minorities of China .…”
Section: Haptoglobinmentioning
confidence: 89%
“…Fig ure I shows the frequencies of HP*1 in some Han populations from different regions of China [3][4][5][6]. A significant geographic varia tion can be seen and there is a particular tend ency for the frequency of HP*1 to increase from the north toward the south of China.…”
Section: Methodsmentioning
confidence: 99%
“…Haptoglobin (HP) has been studied in the most parts of the world fl, 2], but so far there is very scanty HP data available on the Chinese population, especially for different ethnic groups within China [3][4][5]. The aim of the present paper is to present data on HP groups in six different ethnic groups in China.…”
Section: Introductionmentioning
confidence: 99%